Tussock Replacement as a Means of Stabilizing Fire Breaks in Tundra Vegetation - Patterson, William A.; Dennis, John G. (ARCTIC, 1981)
. Although firebreaks in tundra areas will not always be constructed in areas of tussock and dwarf shrub vegetation, the results of our study suggest that vegetation replacement or mulching should be attempted wherever the nature of the topography suggests that post-fire erosion might occur. Natural revegetation of firebreaks in tundra areas is extremely slow, and artificial stabilization techniques may be the only alternative, despite their high cost.